The role of pricing in the Santiago Public Transport System - Jara-Díaz, Sergio (Estudios de Economía, 2016)
The role of pricing a short run tool to induce efficiency in the transport system of Santiago is discussed. The spatial distribution of demand shows that both income and car ownership is discussed. The spatial distribution of demand shows that both income and car ownership are fairly concentrated in the northeast zone.